Value Relevance Of Accountıng Informatıon Of Holdıng Companıes And Non-Holdıng Companıes - M Ali Fikri; Tusta Citta Ihtisan; Iman Waskito (Cita Konsultindo Research Center, 2024)
A holding company is a holding company that owns several shares of other companies and a non-holding company is an independent company and does not control other companies. Value leverage is understood as the ability to explain accounting number information, namely whether the accounting number has a value that is beneficial to investors, and more emphasized, whether the accounting number is indeed a relevant value explaining the stock price in the securities market. This study aims to find the relationship between the relevance of value between holding and non-holding companies using a sample of 175 manufacturing companies on the IDX through testing the usefulness of accounting profit information that affects investor decisions in the capital market. The test results show that there is a difference in value relevance between holding and non-holding companies.